Evaluating the Fire Accidents and Safety Challenges in the Ready-Made Garment Industry of Bangladesh from 2000 to 2024 - Saha, Pooja; Salsabil, Nishat; Zaman, Takia; Hossain, Md Faruk (Indonesian Journal of Geography, 2025)
The readymade garment factory fires have become major concern in the industrial sector of Bangladesh by placing tremendous pressure on the nation's impoverished garment workers. The garment workers are suffering from fatalities, serious injuries, and loss of livelihood. This study's main objective is to examine how Bangladesh's garment industry is vulnerable to fire risks from 2000 to 2024. The majority of the data and information used in this study were collected from secondary sources, including governmental documents and non-governmental organizations. Since the garment business first emerged in Bangladesh, it has faced several difficulties, including fire, which has significant national and international implications. Most factories are situated in close proximity to one another in fire-prone districts, and factory authorities often neglect to take necessary safety precautions. A series of fire accidents occurred in the country over the period and often captured international headlines. Therefore, it is very important to adopt effective measures, such as implementing realistic safety strategies, emphasizing mitigation, ensuring basic safety equipment in factories, providing training to factory staff, and upholding international standards to prevent fires in factories.